A study into the potential of GPUs for the efficient construction and evaluation of Kriging models. (July 2016) - Toal, David
Abstract The surrogate modelling technique known as Kriging, and its various derivatives, requires an optimization process to effectively determine the model's defining parameters. This optimization typically involves the maximisation of a likelihood function which requires the construction and inversion of a correlation matrix dependent on the selected modelling parameters. The construction of such models in high dimensions and with a large numbers of sample points can, therefore, be considerably expensive. Similarly, once such a model has been constructed the evaluation of the predictor, error and other related design and model improvement criteria can also be costly. The following paper investigates the potential for graphical processing units to be used to accelerate the evaluation of the Kriging likelihood, predictor and error functions. Five different Kriging formulations are considered including, ordinary, universal, non-stationary, gradient-enhanced and multi-fidelity Kriging. Other key contributions include the derivation of the adjoint of the likelihood function for a fully and partially gradient-enhanced Kriging model as well as the presentation of novel schemes to accelerate the likelihood optimization via a mixture of single and double precision calculations and by automatically selecting the best hardware to perform the evaluations on.